Redetermination of the crystal structure of bis(μ2-di-ethyldithiocarbamato-κ3S,S′:S;κ3S:S: S′)-hexacarbonyl-di-rhenium(I), C16H20N2O6Re2S4 - Lee, See Mun *; Lo, Kong Mun *; Heard, Peter *; Tiekink, Edward R. T. * (de Gruyter, 2019)
C16H20N2O6Re2S4, monoclinic, C2/c (no. 15), a = 15.3490(2) Å, b = 11.79920(10) Å, c = 13.33770(10) Å, β = 103.9980(10)°, V = 2343.80(4) Å3, Z = 4, Rgt(F) = 0.0166,wRref(F2) = 0.0445, T = 100(2) K. CCDC no.: 1897176 The crystal structure is shown in the figure. Tables 1 and 2 contain details on crystal structure and measurement conditions and a list of the atoms including atomic coordinates and displacement parameters.